2016
DOI: 10.3390/su8030231
|View full text |Cite
|
Sign up to set email alerts
|

Can Clean Energy Policy Improve the Quality of Alpine Grassland Ecosystem? A Scenario Analysis to Influence the Energy Changes in the Three-River Headwater Region, China

Abstract: Abstract:In past decades, ecological services and functions of alpine grassland in the Three-River Headwater Region (TRHR), Qinghai-Tibetan Plateau, have been severely degraded due to overgrazing and overuse of yak dung as a fuel. Therefore, the eco-migration project has been implemented by the national government for improving eco-environmental quality in this region. This paper examines the carbon cycle change from clean energy use of households and assesses its influence on the local grassland ecosystem. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…China has experienced rapid urbanization over the past decades, which has been accompanied by rapid changes in land use patterns that have affected regional ESs [18,19]. On the one hand, these changes have led to a series of ecological problems [18,20], such as soil erosion [21], reduced carbon storage and water yield [22], deteriorating water quality [23], and the destruction of biodiversity [24]. These ecological problems threaten the sustainable development of urban areas and endanger the health of urban ecosystems [20,25].…”
Section: Introductionmentioning
confidence: 99%
“…China has experienced rapid urbanization over the past decades, which has been accompanied by rapid changes in land use patterns that have affected regional ESs [18,19]. On the one hand, these changes have led to a series of ecological problems [18,20], such as soil erosion [21], reduced carbon storage and water yield [22], deteriorating water quality [23], and the destruction of biodiversity [24]. These ecological problems threaten the sustainable development of urban areas and endanger the health of urban ecosystems [20,25].…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in the usage of yak dung could reduce herdsmen's dependence on yak, and thus help to decrease yak number and to improve the rangeland status. Zhang [26] found that decreases in carbon emission from yak dung due to the decreased number of livestock had improved the rangeland ecosystem and the rangeland status. This is consistent with the findings of a statistically significant relationship between livestock number and the rangeland NDVI in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The model has been used widely in more than 20 countries to obtain accurate calibration and verification results in various ecosystems (Abdalla et al, 2009;Chen et al, 2015;Li et al, 1996Li et al, , 2017Xu et al, 2003;Kariyapperuma et al, 2011;Zhao et al, 2016;Liu et al, 2006;Zhang and Niu, 2016).…”
Section: Dndc Modelmentioning
confidence: 99%